THE VISCERA - Saidnazarova Omongul Bahrom Qizi,; Asatullayev Rustamjon Bakhtiyorovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides a comprehensive overview of the human viscera, exploring their intricate anatomical structures and vital physiological functions. It delves into the complex interplay between various internal organs, highlighting their coordinated roles in maintaining homeostasis and overall bodily health. Furthermore, the paper discusses the clinical significance of visceral studies, encompassing diagnostic methodologies, therapeutic interventions, and pathological considerations relevant to internal medicine and surgery. By integrating contemporary research findings, this work aims to enhance the understanding of visceral systems and their profound impact on human well-being.